Uso de pluviómetro, termómetro y pluviógrafo para observadores de estaciones convencionales - Martinez, Oscar; Urdinol, Jaime; Leiva, Angie (2025)
Infographics created to complement and strengthen the capacities in the use of conventional meteorological station instruments of the Secretariat of Natural Resources and Environment of Honduras